"We don't do credit", Nijera Kori, social mobilisation and the collective capabilities of the poor in rural Bangladesh - Kabeer, Naila (Nijera Kori, 2002)
On the activities of Nijera Kori, non-governmental organization of Bangladesh and its impact on the economic conditions of rural poor of Bangladesh; a study.